Biophotonic sensor design using a 1D defective annular photonic crystal for the detection of creatinine concentration in blood serum. Issue 43 (4th August 2021) - Gandhi, Sakshi; Awasthi, Suneet Kumar; Aly, Arafa H.
Abstract : A new biophotonic sensor composed of a porous silicon (PSi)-based one-dimensional (1D) defective annular photonic crystal (APC) was designed and theoretically investigated using a modified transfer matrix method (TMM) in terms of cylindrical coordinates. Abstract : A new biophotonic sensor composed of a porous silicon (PSi)-based one-dimensional (1D) defective annular photonic crystal (APC) was designed and theoretically investigated using a modified transfer matrix method (TMM) in terms of cylindrical coordinates. The proposed biosensor was found to be capable of sensing very minute variations in the refractive index of blood serum samples of different creatinine concentrations. It can be considered as a useful tool for diagnosing mild to chronic kidney diseases by measuring the creatinine concentration in the blood serum samples of patients. The biosensor design [(AB) N /2 D(AB) N /2 /Si] is composed of two 1D APCs (AB) N /2 associated with a defect layer D of a blood serum sample of thickness d d whose creatinine concentration is to be determined. Both 1D APCs are made up of two alternate PSi layers A and B with porosity ratios of 34% and 87%, respectively. Moreover, our proposed biophotonic sensor demonstrated a high value of sensitivity ( S ) between 637.73 and 640.29 nm per RIU, a quality factor ( Q ) between 1.51 × 10 5 and 0.74 × 10 5, and a figure of merit (FOM) between 2.6 × 10 4 and 1.96 × 10 4 RIU, corresponding to a blood serum sample whose creatinine concentration varied between 80.90 to 85.28 μmol L −1 . The limit of detection (LOD) was of the order of 10 −6 RIU. This low value LOD confirmed that our biosensor is capable of noticing any minute change in the wavelength up to an order of 10 −6 . Compared with previous works, the proposed biosensor design can be easily realized and offers high performance at normal incidence, which allows overcoming the complications involved while achieving a high value of sensitivity in planar PC-based biosensor designs at oblique incidence. Beside this, there is also a possibility to explore this work further for the development of various APC-based biosensing designs with the aim to study various human body fluids.